Management of Vietnam’s Social Development in the Digital Social Context and Super Smart Society - Huu Hoang, Nguyen (VNU Journal of Science: Policy and Management Studies; Vol 37 No 3DO - 10.25073/2588-1116/vnupam.4296, 2021)
“Social development management”, “digital society” or “super smart society” - new academic and practical issues in recent years. Through studying domestic and foreign documents, compared to the specific context of Vietnam, the article was systematized, analyzed and discussed urgent issues of social life for the social development management in Vietnam from the perspective of national digital transformation, the orientation of building a digital society and super smart society. It also proposes ideas and suggests models for reference to help solve these challenges well. This research shows that the revolution in science and technology, recently the 4th Industrial Revolution has created a basic foundation of technology and engineering, promoted an objective transition of state and properties modern society towards digitization and super intelligence. This has created positive and unprecedented changes, but also raises many new problems for each individual, community and the process of current social change management.